High Doses of Halotolerant Gut-Indigenous Lactobacillus plantarum Reduce Cultivable Lactobacilli in Newborn Calves without Increasing Its Species Abundance - Alexander Rodriguez-Palacios; Henry R. Staempfli; J. Scott Weese (International Journal of Microbiology)
To elucidate the ecological effect of high oral doses of halotolerant (resistant to table salt) indigenous-gut bacteria on other commensals early in life, we conducted a culture-based study to quantify the effect of intestinal Lactobacillus plantarum strain of bovine origin (with remarkable aerobic growth capabilities and inhibitory activity against Escherichia coli O157:H7 and F5) on clinical health and gut lactobacilli/coliforms in newborn calves. In a double-blind placebo-randomized trial twelve colostrum-fed calves, consecutively born at a farm, were fed L. plantarum within 12 hours from birth at low (107-8 CFU/day) or high concentrations (1010-11) or placebo (q24 h, 5 d; 10 d follow-up). We developed a 2.5% NaCl-selective culture strategy to facilitate the enumeration of L. plantarum-strain-B80, and tested 384 samples (>1,152 cultures). L. plantarum-B80-like colonies were detected in a large proportion of calves (58%) even before their first 24 hours of life indicating endemic presence of the strain in the farm. In contrast to studies where human-derived Lactobacillus LGG or rhamnosus had notoriously high, but short-lived, colonization, we found that L. plantarum colonized stably with fecal shedding of 6±1 log10·g−1 (irrespective of dose, P>0.2). High doses significantly reduced other fecal lactic acid bacteria (e.g., lactobacilli, P<0.01) and slightly reduced body weight gain in calves after treatment. For the first time, a halotolerant strain of L. plantarum with inhibitory activity against a human pathogen has the ability to inhibit other lactobacilli in vivo without changing its species abundance, causing transintestinal translocation, or inducing clinical disease. The future selection of probiotics based on halotolerance may expand therapeutic product applicability.